(untitled) (Revista Brasileira de História da Educação, 2012)
Neste artigo, pretendo promover uma análise do Programa para as Escolas Primárias do Distrito Federal, elaborado durante a Reforma Fernando de Azevedo de 1927 a 1930, procurando, a partir da constituição dos saberes escolares selecionados, particularmente no que concerne Ã disciplina de Educação Higiênica, identificar as diferentes representações de infância que configuraram como modelo para formação de um “novo cidadão” a ser forjado na capital do país. Abstract In this article I intend to promote the analysis of Program to Primary Schools of Federal District, elaborated during Fernando de Azevedo’s Reform from 1927 to 1930, searching, from the constitution of selected school knowledges, in particular, concerning, discipline of Hygienic Education, to identify the different representations of childhood that showed up as a model to development of the “new citizen” to be forged in the capital country. Keywords School Knowledges; Reform of Education; Childhood; Hygienic Education